Distributive Justice, Culture and Self-Concept: A Comparison between Spain and Costa Rica - Chaverri Chaves, Pablo; Fernández Sedano, Itziar (Actualidades en Psicología, 2025)
Objective. To analyze distributive justice in terms of cultural individualism-collectivism, as well as independent and interdependent self-perception. Method. The sample consisted of Spaniards and Costa Ricans (N = 859; M = 33.28; SD = 13.12 years; 37.9% were male and 62.1% female). Analysis of variance with post-hoc comparisons was performed to determine how the combination of cultural context and self-perception influences distributive justice operationalized with the ultimatum game. Results. Participants who live in a collectivist cultural context are more accepting of unequal proposals, while those with an independent self-perception reject the most unjust ones, and those who are interdependent and collectivist (vs. independent and individualistic) have less distributive justice.